Food Safety Awareness and Practices among Adult Women and Its Association with Acute Diarrheal Disease in their Household in a Rural Area of Coimbatore, Tamil Nadu - Darshan Manoj; Sandhiya Venkatesan; Jenit Osborn; Satheesh (Journal of Epidemiology and Public Health, 2024)
Background: Food safety is a paramount concern in today's world, given its critical implications for public health. Contaminated food can lead to severe illnesses and outbreaks, affecting individuals of all ages and backgrounds. Therefore, the study was conducted to assess the level of food safety awareness and attitude among adult women.Subjects and Method: A cross-sectional study was conducted in the rural field practice area of PSG Institute of Medical Sciences & Research, Coimbatore from December 2019 to May 2020. A total of 400 participants were selected using systematic random sampling. A pretested, validated study questionnaire was used to collect the data. Data analysis is done by the estimation of disease risk associated with exposure and calculating the p<0.050 proving the statistical association between exposure status and disease occurrence.Results: Half of them (50%) had adequate knowledge regarding food safety practices and 60% adequately practiced them. Washing hands after using the toilet was practiced by 80.8%. washing hands before eating food was practiced by 74.3%. Rat and fly menace were present in 20.5% and 23.3% respectively. Acute Diarrheal Disease was present in 19.3% of households. The presence of acute diarrhoeal disease (ADD) was found to be significantly higher in those who were not washing their hands after using the toilet, presence of flies and rats in the kitchen, and having inadequate knowledge and practices regarding food safety.Conclusion: Though half of the women demonstrated awareness of food safety principles, the study revealed that actual implementation of safe practices remains inadequate. The association of diarrheal diseases with poor handwashing habits, as well as the presence of pests in the kitchen, emphasizes the critical need for targeted interventions to address these issues